Frontiers in Protein Folding and Related Areas - in Memory of Professor Sir Christopher M. Dobson (1949-2019) - Kuwajima, Kunihiro; Okamoto, Yuko; Knowles, Tuomas; Vendruscolo, Michele (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue is dedicated to the memory of the late Professor Sir Christopher M. Dobson (1949-2019), who made outstanding contributions to the advancement of studies on protein folding and its related areas and played an irreplaceable role in the promotion of protein science. This reprint contains 24 recent research papers (17 original papers and 7 review papers) on protein folding, misfolding, and amyloid formation, which often lead to various human diseases.